Ultrasound‐guided vascular access for CIED implantation: A step‐by‐step guide. (23rd February 2023) - Salcedo, Jonathan
Abstract: Introduction: Vascular access is required for most cardiac electrophysiology procedures. Over the past 2 decades, ultrasound guidance has increased in utilization as the primary method for assisting operators in gaining access to cardiac implantable electronic device (CIED) implantation. Methods: Ultrasound guidance using a technique that includes both short‐axis and long‐axis views combined with a twisting needle motion after maximal tenting provides an extremely safe and reproducible technique for vascular access for all CIED procedures. Results and Conclusions: In this manuscript and accompanying videos, a step‐by‐step guide is explained for optimal ultrasound‐guided visualization and needle maneuver technique to maximize safety and efficiency for vascular access in all CIED procedures.